Appropriate boundary conditions for a pressure driven boundary layer. Issue 142 (July 2015) - Richards, P.J.; Norris, S.E.
Abstract: Velocity and turbulence property profiles are derived for an equilibrium pressure driven atmospheric boundary layer for RANS CFD models using the k-ε, k-ω and SST turbulence models. By comparison with the Deaves and Harris model it is shown that such a pressure driven boundary layer is a reasonable model for the lower half of the atmospheric boundary layer where the shear stress decreases approximately linearly with height. The profiles derived satisfy equilibrium of the momentum and both turbulence property conservation equations. It is shown that using these profiles as the inlet conditions on an empty domain results in outlet profiles which are almost identical to the inlet values. It is also shown that using profiles intended for a shear driven situation, but without the driving shear stress, leads to significant changes as the flow relaxes towards matching the free slip boundary condition at the top of the domain.